1994
DOI: 10.1177/073490419401200304
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Upholstery Fabric Properties on Fabric Ignitabilities by Smoldering Cigarettes

Abstract: Five-hundred popular upholstery fabrics were obtained from commercial fabric shops in North Carolina. The ignitability of each upholstery fabric was characterized using a particular smoldering cigarette in a specified protocol with six replications. If one or more of the smoldering cigarettes resulted in smoldering of the fabric, the fabric was classified as ignitable. Of the 500 fabrics, 355 were found to be non-ignitable and 145 were classified as ignitable. The differences between the properties of ignitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 6 publications
2
29
0
Order By: Relevance
“…A previous survey of 500 upholstery fabrics [4][5][6], carried out by the Cigarette Ignition Propensity Joint Venture', indicated that the combination of physical properties (weight, density, air permeability, etc.) of the cotton ducks lies outside those encountered in upholstery fabrics intended for home use.…”
Section: Greensboro Nc 27401mentioning
confidence: 99%
See 2 more Smart Citations
“…A previous survey of 500 upholstery fabrics [4][5][6], carried out by the Cigarette Ignition Propensity Joint Venture', indicated that the combination of physical properties (weight, density, air permeability, etc.) of the cotton ducks lies outside those encountered in upholstery fabrics intended for home use.…”
Section: Greensboro Nc 27401mentioning
confidence: 99%
“…Ignitable fabrics have certain characteristics that separate them from those that do not ignite [1][2][3][4][5][6][7][8][9][10][11][12]. Specifically, they are composed entirely or predominately of cellulosic fibers (cotton, rayon, blends of these two, or perhaps, linen), generally weigh at least 8 oz/yd2, and contain enough sodium or potassium (generally > 1000 ppm) to sustain a smoldering ignition [4][5][6].…”
Section: Experimental Fabric Procurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Ihrig et al [3] defined the term &dquo;fabric proclivity,&dquo; based on the average smolder times of yarns in a fabric, the term is an excellent predictor of a fabric's ignition potential. Dwyer et al [4] reported that the most ignitable fabrics toward a smoldering-cigarette heat source were 100 percent cellulosic, with weights above 15 oz/yd2, and having a combined sodium and potassium level in excess of 1500 ppm.…”
mentioning
confidence: 99%
“…Other studies have concentrated on the role that alkali metal ions play in promoting cigarette-induced ignitions of upholstery fabrics [3][4][5][6]. Ihrig et al [3] defined the term &dquo;fabric proclivity,&dquo; based on the average smolder times of yarns in a fabric, the term is an excellent predictor of a fabric's ignition potential.…”
mentioning
confidence: 99%